2018
DOI: 10.3389/fendo.2017.00365
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin/Kisspeptin Receptor System in the Ovary

Abstract: Kisspeptins are a family of neuropeptides that are critical for initiating puberty and regulating ovulation in sexually mature females via the central control of the hypothalamic–pituitary–gonadal axis. Recent studies have shown that kisspeptin and its receptor kisspeptin receptor (KISS1R) are expressed in the mammalian ovary. Convincing evidence indicates that kisspeptins can activate a wide variety of signals via its binding to KISS1R. Experimental data gathered recently suggest a putative role of kisspeptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 156 publications
(206 reference statements)
5
74
1
4
Order By: Relevance
“…Emerging evidence on FF- KP levels and its relationship with the female reproductive system reflects the importance of intraovarian KP in follicular development, oocyte maturation, and ovulation. Decreased concentration of follicular KP can adversely affect ovarian function, female reproduction, and fertility [ 26 ]. It has been observed that granulosa cells (GC) are one of the major sites for KP synthesis in rats, as Kiss1mRNA expression was found to be significantly higher in the GCs compared with the theca cells and other ovarian cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence on FF- KP levels and its relationship with the female reproductive system reflects the importance of intraovarian KP in follicular development, oocyte maturation, and ovulation. Decreased concentration of follicular KP can adversely affect ovarian function, female reproduction, and fertility [ 26 ]. It has been observed that granulosa cells (GC) are one of the major sites for KP synthesis in rats, as Kiss1mRNA expression was found to be significantly higher in the GCs compared with the theca cells and other ovarian cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased concentration of follicular KP can adversely affect ovarian function, female reproduction, and fertility [ 26 ]. It has been observed that granulosa cells (GC) are one of the major sites for KP synthesis in rats, as Kiss1mRNA expression was found to be significantly higher in the GCs compared with the theca cells and other ovarian cells [ 26 ]. In our study, KP levels in FF were higher than maximum serum KP levels in women, which is similar to a study that also observed higher FF KP concentration than serum levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Новые данные указывают на потенциальную роль гипоталамического нейропептида в модулировании активности различных систем в головном мозге и многих периферических органах. Несколько исследований показали, что кисспептин и его рецептор экспрессируются в различных тканях и могут оказывать прямое аутокринно-паракринное действие, в том числе в репродуктивных органах: яичник, плацента [18].…”
Section: Discussionunclassified
“…All kisspeptins contain the RFamide motif that can bind and activate KISS1R. 4,5 The most abundant kisspeptin in the human circulation is kisspeptin-54. 6 KISS1R belongs to the G-protein-coupled receptor family that was first identified as an orphan receptor in the rat brain.…”
Section: Introductionmentioning
confidence: 99%